Fire resistance of ultra-high performance fibre reinforced concrete due to heating and cooling - Fadzli, Mohamed Nazri; Ramadhansyah, Putra Jaya; Badorul Hisham, Abu Bakar; Raudhah, Ahmadi (EDP Sciences, 2016)
This study investigated the performance of ultra-high performance fibre reinforced concrete (UHPFRC) at elevated temperatures. The specimens were exposed to high temperatures, specifically 200, 400, and 600 °C, for 2 h.The fire resistance performance of the specimens was classified on the basis of their compressive strength, spalling, and weight loss; residual strength after heating was also examined. Results showed that UHPFRC processes excellent fire resistance in terms of flame spread and fire growth. While strength loss was not significant at low temperatures, the specimen subjected to high temperature spalled severly and showed deterioration because of heat.